2020
DOI: 10.3390/ijerph17176362
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Severity and Susceptibility towards Leptospirosis Infection in Malaysia

Abstract: Background: Perceived severity and susceptibility refers to one’s belief of the seriousness and the risk of contracting a specific disease. It is an essential study in public health as it assists in the understanding of the motivating factors towards disease prevention. This qualitative study aimed to explore perceived severity and susceptibility towards leptospirosis infection among respondents in two states of Malaysia. Methods: Focus group discussions using the phenomenology approach was conducted involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…They are therefore extra careful to avoid bites from mosquitoes possibly carrying dengue. This component of HBM has a profound effect on the course of other communicable diseases in this country [ 44 ]. Perceived benefit was the last latent factor in the risk perception domain; this is the individual’s perception of actions intended to reduce the threat of disease.…”
Section: Discussionmentioning
confidence: 99%
“…They are therefore extra careful to avoid bites from mosquitoes possibly carrying dengue. This component of HBM has a profound effect on the course of other communicable diseases in this country [ 44 ]. Perceived benefit was the last latent factor in the risk perception domain; this is the individual’s perception of actions intended to reduce the threat of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other studies have supported the viability of both constructs in facing disease contexts [ 59 , 60 ]. A great majority of people first assessed their susceptibility and severity, other than perceived benefits and barriers, when encountering certain diseases [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, a maladaptive reaction to the pandemic is linked to an increased psychological burden due to increased uncertainties and anxiety resulting from the curfew and new living conditions. Mass media and social media have been implicated in both reactions [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Health Belief Model [18], the perceived severity and susceptibility explain how individuals' beliefs predict their response to a disease. Depending on how much an individual feels susceptible or likely to suffer significant harm from an illness, one may adopt or disregard health-protecting behaviors [14,19]. Petrie and Weinman found that the perception of illness influenced individuals' emotional response to a disease threat, coping behaviors, and adherence to protective and preventive measures [20].…”
Section: Introductionmentioning
confidence: 99%